Suicide risk, personality disorder and hospital admission after assessment by psychiatric emergency services - Van Veen, Mark (BMC Psychiatry, 2019)
BACKGROUND: The main objectives of the mobile Psychiatric Emergency Services (PES) in the Netherlands are to assess the presence of a mental disorder, to estimate risk to self or others, and to initiate continuity of care, including psychiatric hospital admission. The aim of this study was to assess the associations between the level of suicidality and risk of voluntary or involuntary admission in patients with and without a personality disorder who were presented to mobile PES. METHODS: Observational data were obtained in three areas of the Netherlands from 2007 to 2016. In total, we included 71,707 contacts of patients aged 18 to 65 years. The outcome variable was voluntary or involuntary psychiatric admission. Suicide risk and personality disorder were assessed by PES-clinicians. Multivariable regression analysis was used to explore associations between suicide risk, personality disorder, and voluntary or involuntary admission. RESULTS: Independently of the level of suicide risk, suicidal patients diagnosed with personality disorder were less likely to be admitted voluntarily than those without such a diagnosis (admission rate .37 versus .46 respectively). However, when the level of suicide risk was moderate or high, those with a personality disorder who were admitted involuntarily had the same probability of involuntary admission as those without such a disorder. CONCLUSIONS: While the probability of voluntary admission was lower in those diagnosed with a personality disorder, independent of the level of suicidality, the probability of involuntary admission was only lower in those whose risk of suicide was low. Future longitudinal studies should investigate the associations between (involuntary) admission and course of suicidality in personality disorder.